Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Peserta Didik Kelas VII Materi Ekologi dan Keanekaragaman Hayati - Rohmawati, Ifatur; Hanikah, Hanikah; Sumiri, Sumiri (STKIP HARAPAN BIMA, 2025)
This research aims to improve student learning outcomes through the application of the problem based learning model in class VII Ecology and Biodiversity material. The research methods are classroom action research (PTK), and location. The research was conducted at SMPN 1 Plered with a total of 33 students as research subjects. Data collection techniques using tests. The test aims to obtain student learning outcomes carried out during the pre-cycle, cycle I and cycle II. The instrument used is multiple choice questions. Based on analysis data obtained in the first cycle of students get an average score of 70%, then in cycle II students get an average score of 85%. Through the results obtained, the application of the Problem Based Learning learning model is effective in improving student learning outcomes. Implementing learning using the Problem Based Learning (PBL) learning model is very helpful in improving student learning outcomes, shown by the increase in average scores in each cycle.